Mechanisms of Cadmium Toxicity: Metabolomics and Medical Approach - Salaudeen, Abdulwasiu Olawale; Olawore, Yemisi Ajoke; Yakubu, Hajara (African Journal of Biochemistry and Molecular Biology Research, 2025)
Heavy metals are harmful pollutants due to their toxicity at low concentrations, persistent nature and non-biodegradability that have attracted widespread attention. Heavy metals, such as arsenic, cadmium, chromium, lead and mercury are known to be toxic to plants and animals. Cadmium is a highly toxic heavy metal that adversely affects most organ systems. It is commonly found in humans, with primary sources of exposure being cigarette smoke, welding, and contaminated food and beverages. There is compelling evidence from recent studies linking exposure to cadmium to the development of cancer, liver damage, renal failure, skin and hair abnormalities and cardiovascular problems. Cadmium have been shown in epidemiological, basic, and clinical studies to increase the generation of reactive oxygen species. This, in turn, can aggravate the generation of reactive oxygen species and cause inflammation, which can lead to endothelial dysfunction, disruption of ion homeostasis and epigenetic modifications. According to recent research, metabolomics can be used to uncover possible biomarkers and biological pathways, as well as to get molecular snapshots of organisms following environmental exposure to stressors like cadmium. Thus, the purpose of this review is to give readers a thorough understanding of the biochemistry and mechanisms that give rise to cadmium toxicity. We also address antioxidants and other substances that have protective properties against cadmium toxicity, as well as the molecular underpinnings of cadmium-induced cellular damage.